2015
DOI: 10.1016/j.margeo.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Classifying seabed sediment type using simulated tidal-induced bed shear stress

Abstract: An ability to estimate the large-scale spatial variability of seabed sediment type in the absence of extensive observational data is valuable for many applications. In some physical (e.g., morphodynamic) models, knowledge of seabed sediment type is important for inputting spatially-varying bed roughness, and in biological studies, an ability to estimate the distribution of seabed sediment benefits habitat mapping (e.g., scallop dredging). Although shelf sea sediment motion is complex, driven by a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…Tidal laminations (rythmites), which are formed by varying amounts and types of sediment deposited on the flood and the ebb tide (e.g., Dalrymple, ), can be used to infer tidal components and longer‐term variations but are highly localized in time and space and can give a range of potential tidal amplitudes (e.g., Tanavsuu‐Milkeviciene & Plink‐Bjorklund, ; Williams, ). Attempts have also been made to reconstruct tidal dynamics by linking sea bed sediment types from sediments cores to bed shear stress in order to infer tidal current strength (Ward et al, ) but were hampered by limitations of the sedimentary records. Studies reconstructing changes in stratification in paleo–shelf seas from plankton assemblages (e.g., Scourse et al, ; Woods et al, ) can provide an indication of the strength of tidal currents by tracking tidal mixing fronts but again only provide an indication of regional tidal conditions.…”
Section: Past Changes In Tidesmentioning
confidence: 99%
“…Tidal laminations (rythmites), which are formed by varying amounts and types of sediment deposited on the flood and the ebb tide (e.g., Dalrymple, ), can be used to infer tidal components and longer‐term variations but are highly localized in time and space and can give a range of potential tidal amplitudes (e.g., Tanavsuu‐Milkeviciene & Plink‐Bjorklund, ; Williams, ). Attempts have also been made to reconstruct tidal dynamics by linking sea bed sediment types from sediments cores to bed shear stress in order to infer tidal current strength (Ward et al, ) but were hampered by limitations of the sedimentary records. Studies reconstructing changes in stratification in paleo–shelf seas from plankton assemblages (e.g., Scourse et al, ; Woods et al, ) can provide an indication of the strength of tidal currents by tracking tidal mixing fronts but again only provide an indication of regional tidal conditions.…”
Section: Past Changes In Tidesmentioning
confidence: 99%
“…Physical sediment characteristics are more important than biological factors for determining bed stability in the Celtic Sea (Thompson et al, ). Ward et al () show regional bed shear stress patterns at 1.1‐km resolution. This and aforementioned modeling studies focus on tide‐induced bed shear stress, neglecting surface waves.…”
Section: Study Areamentioning
confidence: 99%
“…Tidal and wave energy levels at the seabed should strongly influence mud, sand and gravel percentages. Large grain sizes require more energy to dislodge from the seabed, and therefore high bed shear stress is associated with increases in average grain size and reductions in mud content (Ward et al, 2015;Heath et al, 2016). There is scarce evidence to determined if seabed composition is influenced by year-round bed shear stress or individual high-energy events.…”
Section: Environmental Predictors For Random Forest Models and Model mentioning
confidence: 99%
“…However, this is unlikely to be true everywhere. Ward et al (2015) have argued that the coarser sediments found south-east of Ireland were inherited from prior stress regimes. Furthermore, the Irish Sea has linear tidal sand ridges, which are likely relics from an earlier more energetic stress regime (Uehara et al, 2006;Scourse et al, 2009).…”
Section: Limitations and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation